Potential trophic cascades triggered by the barred owl range expansion - Samantha R. Holm; Barry R. Noon; J. David Wiens; William J. Ripple (Wildlife Society Bulletin)
ABSTRACT Recently, the barred owl (Strix varia) has expanded its range into the Pacific Northwest of the United States resulting in pronounced effects on the demography and behavior of the northern spotted owl (S. occidentalis caurina). The range expansion has brought together historically allopatric species, creating the potential for significant changes in the avian predator community with possible cascading effects on food‐web dynamics. The adverse effects of the barred owl on the behavior and demography of the northern spotted owl are well‐documented, but little is known about the immediate and long‐term effects changes in the predator community may have on native species composition and ecosystem processes. Based on northern spotted owl and barred owl selection for diet and habitat resources, there is a potential for trophic cascades within the region's predator and prey communities, differing responses by their shared and unique prey species, and possible direct and indirect effects on ecosystem processes. We explored the possible ecological consequences of the barred owl range expansion to wildlife communities of the Pacific Northwest based on the theoretical underpinnings of predator–prey relationships, interspecific competition, intraguild predation, and potential cascading trophic interactions. Negative effects on fitness of northern spotted owls because of interspecific competition with barred owls are strong selection forces that may contribute to the regional extinction of the northern spotted owl. In addition, we posit that shared prey species and those uniquely consumed by barred owls, along with other competing native predators, may experience changes in behavior, abundance, and distribution as a result of increased rates of predation by rapidly expanding populations of barred owls. © 2016 The Wildlife Society.